1998
DOI: 10.1161/01.res.83.3.279
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Constitutive and Inducible Nitric Oxide Synthases in the Vascular Wall of Young and Aging Rats

Abstract: Two NO synthase (NOS) isoforms have been described in vessels, an endothelial constitutive NOS (eNOS) and an inducible NOS (iNOS). The purpose of the present study was to examine the endothelium-dependent and endothelium-independent hypotensive response in aging rats, analyzing the ability of their vessels to produce NO. The studies were performed in 2 groups of euvolemic, conscious, male Wistar rats: aging rats (n=20, 18 months old) and young rats (n=20, 5 months old). The hypotensive responses to acetylcholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

25
199
0
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(236 citation statements)
references
References 25 publications
25
199
0
8
Order By: Relevance
“…The role of the L-arginine/NO pathway in the pathophysiology of vascular aging is controversial. Both reduced levels of eNOS mRNA (Challah et al, 1997) and increased eNOS enzyme expression combined with reduced activity (Cernadas et al, 1998) have been reported. Therefore, our first aim was to clarify whether age-associated endothelial dysfunction is causally related to alterations of the L -arginine/NO system.…”
Section: Introductionmentioning
confidence: 94%
“…The role of the L-arginine/NO pathway in the pathophysiology of vascular aging is controversial. Both reduced levels of eNOS mRNA (Challah et al, 1997) and increased eNOS enzyme expression combined with reduced activity (Cernadas et al, 1998) have been reported. Therefore, our first aim was to clarify whether age-associated endothelial dysfunction is causally related to alterations of the L -arginine/NO system.…”
Section: Introductionmentioning
confidence: 94%
“…Animals were age-matched to minimize differences in both the angiogenic response (36) and vascular NOS III expression (37).…”
Section: Tumor Implantsmentioning
confidence: 99%
“…Most previous studies suggested that decreased endothelialdependent vasodilatation was mainly associated with down regulation of eNOS and endogenous NO [13,14] . Recent research found that, iNOS expression increased in vascular tissue of aged rats [15,16] . However, it is unclear that whether elevated iNOS plays a role in the decline of endothelium-dependent vasodilatation.…”
Section: Introductionmentioning
confidence: 99%